Pemanfaatan Rusun Umum Oleh Non-MBR Kota Surabaya Ditinjau Menurut UU 20/2011 Tentang Rumah Susun - Tanta, Jerisa Frabel (JURNAL MINUTA, 2024)
In Indonesia, the government has initiated national development as a way to preserve the well-being of every Indonesian citizen in a just and equitable manner consistent with Pancasila values. In this regard, one of the key components that complies with the mandate in Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia is the community's ability to meet housing needs. The government has created an alternate scheme by building public flats, particularly in terms of supplying housing for low-income comunities. Despite the fact that its construction was built for low-income communities, many of these flats are still not being utilized as planned. One illustration is that public flats in Surabaya is still occupied by a lot of individuals who are not exactly part of the low-income comunities grouping. As a result, there is an indication that there is a misalignment between the target audience of flats and the relevant regulations. Hence, This study discussed about whether the use of flats for Low-Income Communities in Surabaya has complied with UU Number 20 of 2011 regarding Public Flats, and what the legal implications are for residents who are not low-income comunities but live in public flats .